Assessment of Egyptian Local Sheep and Goat Productivity Under the Environmental Conditions of Coastal Zone of Western Desert and Upper Egypt - Taha Abdelsabour; Hussein Mansour; Samir Messad; Manal Elsayed; Adel Aboulnaga; Veronique Alary (Arab Universities Journal of Agricultural Sciences, 2023)
Livestock plays a significant role in food production, income generation, soil quality, transportation and the overall welfare of communities, especially in developing nations. Sheep and goats are vital sources of food, livelihood and urgent financial needs. Researching livestock practices can help optimize production, enhance productivity, and improve market access, ultimately boosting the economic well-being of developing communities. Research is needed to identify climate-resilient livestock practices, develop drought-resistant breeds, and optimize feed management strategies. By enhancing the resilience of livestock systems, research can help safeguard food security and livelihoods in the face of climate change. Climate change, evidenced by temperature changes and increased extreme weather events, negatively impacts traditional farming systems and livestock production by affecting pastures, feeds, water quality and livestock diseases. Breeds of the Coastal Zone of Western Desert (CZWD)  such as the Barki sheep and goat as well as the Saidi breed in Upper Egypt (UE), have adapted to these harsh conditions and are crucial for smallholders. However, there's an information gap regarding these breeds' productivity in smallholder systems. This study utilizes the Twelve Month Monitoring (12MO) survey to estimate the productivity and demographic parameters of these breeds from 2018 to 2020.